FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI KURANG PADA BALITA DI PUSKESMAS DOI-DOI KABUPATEN BARRU - Wilda Rezki Pratiwi; St. Hasriani (Universitas Islam Madura, 2023)
Nutritional problems in children can be caused by several factors such as unbalanced food and infectious diseases, food security in families that is lacking to meet the food needs of all family members, both in number and nutrition. Nutritional problems are also caused by a family's inadequate ability to provide time, attention and support for children so that they can grow and develop as well as possible both mentally, socially and physically. The research was conducted from March 8 to April 8 2022. This type of research is an observational method with a Cross Sectional Study approach. The population in this study was 373. The samples in this study were 48 people. The results showed that there was a significant relationship between knowledge and malnutrition status with a value of p=0.000. The results showed that there was a significant relationship between perceptions and malnutrition status with a value of p = 0.036. The results showed that there was a significant relationship between parenting style and malnutrition status with p=0.001. The results showed that there was a significant relationship between income and malnutrition status with a value of p=0.000. Conduct counseling by incorporating material on how to feed toddlers, nutrients contained in food, food intake that should be fulfilled to prevent infectious diseases and growth disorders in toddlers